RUANG TERBUKA HIJAU DALAM MITIGASI PERUBAHAN IKLIM GREEN OPEN SPACE IN CLIMATE CHANGE MITIGATION - Yusriani Sapta Dewi (Jurnal Ilmiah Pendidikan Lingkungan dan Pembangunan, 2010)
Climate change is any substantial change in Earth’s climate that lasts for an extended period oftime. Global warming refers to climate change that causes an increase in the average temperature of thelower atmosphere. Global warming is the combined result of anthropogenic (human-caused) emissionsof greenhouse gases and changes in solar irradiance, while climate change refers to any change in thestate of the climate that can be identified by changes in the average and/or the variability of its properties(e.g., temperature, precipitation), and that persists for an extended period, typically decades or longer.Green open space is one of solution for climate change mitigation.